Perancangan E-Book Sebagai Media Pengenalan Permainan Tradisional Kepulauan Riau Kepada Guru Dan Orang Tua - Angelia, Angelia; Setiawan, Hendra; Lukman, Christine Claudia (Fakultas Desain Universitas Komputer Indonesia, 2025)
Playing is important for the developmental stages of early childhood, as it can enhance intelligence in strategy planning and build a child's character education. Character education for children can be formed through playing traditional games. Indonesia is a country that has many traditional games that have been played for generations, but their existence is starting to fade due to the rapid flow of modernization and increasingly advanced technology, making today's children prefer playing gadget games and making them mature faster than their age. To prevent children from forgetting traditional games and becoming individualistic, the approach to playing can be started from the closest adults such as teachers and parents. The researcher has chosen one region, namely the Riau Islands, to make an E-Book containing traditional games from the Riau Islands which includes information about the games, number of players, tools and materials, how to make them and how to play them, in order to bring back children's love for traditional games in Indonesia and is expected to have good habits so that they can become children with strong character in their behavior.